Those Who Don't Return: Improving Efforts to Address Tuberculosis Among Former Miners in Southern Africa. (May 2019) - Smith, Jonathan; Blom, Paul
Despite increasing awareness regarding the role of oscillating migration in the mining industry as a major driving force in the spread of tuberculosis (TB) throughout southern Africa, very little work has focused on the historical and contextual factors which may contribute to former migrant miners' present-day risk of TB. Most research regarding migration-related and occupational influences on TB has been done on current miners still employed by the mining industry. Through both a historical and contemporary lens, this paper explores and elucidates the need to address the TB epidemic among former migrant mine workers and provides considerations to improve current interventions among this critical population.